Reduced childhood social attention in autism model marmosets predicts impaired social skills and inflexible behavior in adulthood - Nakagami, Akiko; Yasue, Miyuki; Nakagaki, Keiko; Nakamura, Madoka; Kawai, Nobuyuki; Ichinohe, Noritaka (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social and communication impairments and restricted and repetitive behavior. Although currently no established cure exists for ASD, early intervention to the deficits of attention to other individuals is expected to reduce the progression of ASD symptoms in later life. In order to confirm this hypothesis and improve early therapeutic interventions, it is desirable to develop an animal model of ASD in which social attention is impaired in childhood and ASD-like social behavior is observed in adulthood. However, rodent models of ASD have difficulty in recapitulating the deficit of gaze-based social attention. In this study, we examined the direction of gaze towards other conspecifics during childhood and puberty in a three-chamber test setting using an ASD model of marmoset produced by maternal exposure to valproic acid (VPA). We also conducted a reversal learning test in an adult VPA-exposed marmoset as an indicator of perseveration, a core symptom of ASD that has not previously been investigated in this model. The results showed that time spent gazing at other conspecifics was reduced in VPA-exposed marmosets in childhood, and adults displayed rigidity of response. In a longitudinal study using the same animals, deficits in social attention in childhood correlated well with ASD-like social disturbance (inequity aversion and third-party reciprocity) and inflexible behavior in adulthood. Since VPA-exposed marmosets exhibit these diverse ASD-like behaviors that are coherent from childhood to adulthood, VPA-exposed marmosets will provide a valuable opportunity to elucidate mechanisms for early intervention and contribute to the development of early therapies.